-(+8)-(-16)=
-(+13)+(-9)=
+(-7)-(+13)=
-(-9)+(-9)=
+(-5)-(-6)=
-(-2)+(-12)=
+(+14)-(-7)=
(-10)+(+11)=
Soluções para a tarefa
Respondido por
2
Resposta:
Explicação passo a passo:
-(+8)-(-16)= - 8 + 16 = 8
-(+13)+(-9)= -13 - 9 = - 22
+(-7)-(+13)= -7-13= - 20
-(-9)+(-9)= 9-9= 0
+(-5)-(-6)= - 5 + 6 = 1
-(-2)+(-12)= 2-12= - 10
+(+14)-(-7)= 14 + 7 = 21
(-10)+(+11)= -10+11= 1
Perguntas interessantes
Matemática,
7 meses atrás
Sociologia,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Inglês,
1 ano atrás
Física,
1 ano atrás
Biologia,
1 ano atrás